Proficiency and implementation associated with non-communicable diseases among secondary school students in Bangladesh - Farhana Akter, Adnan Mannan, Nasrin Lipi, Nor Azlina A. Rahman, Halyna Lugova, Md Ahsanul Haq, Mainul Haque (Journal of Applied Pharmaceutical Science, 2023)
The burden of non-communicable diseases (NCDs) is growing swiftly in low-resourced countries. In Bangladesh, a high prevalence of unhealthy lifestyles has been observed among its population. This study aimed to measure the knowledge and practices related to NCDs and associated factors among Bangladeshi secondary school-going students. A cross-sectional study was conducted among secondary students from all administrative regions. Data were collected through questionnaires in-person, over telephone interviews, and online surveys. Data were analyzed descriptively by frequencies and percentages. The Pearson chi-square test was used to examine the association between the variables. A multiple logistic regression model was introduced to identify the predictors of healthy lifestyle practices. A total of 1,744 students were included in this study. Several gaps in knowledge and insufficient healthy practices were revealed. In the multiple linear regression analysis, the type of school, place of residence, parent’s educational level, and monthly income accounted for variability in the level of knowledge about NCDs. Gender, type of school, and monthly income were independent predictors of healthy lifestyle practices. Health educational programs on risk factors of NCDs and healthy lifestyles should be incorporated into the core school curriculum of all schools in Bangladesh. The programs should target economically disadvantaged populations and ethnic minorities to address social inequalities.
Keywords: Non-infectious diseases, comprehension, teenagers, secondary school students, adolescents, Bangladesh